ChemInform Abstract: Orientation Control over Bent‐core Smectic Liquid Crystal Phases. Issue 32 (24th July 2014) - Kim, Hanim; Kim, Yun Ho; Lee, Sunhee; Walba, David M.; Clark, Noel A.; Lee, Sang Bok; Yoon, Dong Ki
Abstract: Review: 84 refs.